Efecto del nivel de proteína en la dieta de alimentos balanceados sobre el crecimiento y la alimentación en alevines de Guanchiche (Hoplias microlepis) en cautiverio en el sector los Sauces - López Lema, Melanie Trinidad (2021)
The production of fry is an activity that allows the introduction of aquaculture species and the strengthening of endangered species, thus contributing to the food industry for the world population; therefore, it is important to know about the conditions and adequate feeding for their optimal development in their first stage as fry, where all the levels of protein, vitamins and adequate environmental conditions must be provided for a good productive performance in their subsequent growth. In this sense, the objective of the research was to evaluate the productive behavior and morphometric characteristics of guanchiche (Hoplias microlepis) fry fed with different levels of protein. The duration of the research was 120 days, using five treatments with commercial protein levels of 28%, 30%, 40%, 45% and 50%, with 3 replicates. A completely randomized design (CRD) was applied, with 90 guanchiche fry distributed in groups of 6 units per replicate. The variables were subjected to analysis of variance and the TUKEY test (P<0.05). The results in the zootechnical parameters show a significant difference in the treatments T3 and T4 with 30 and 45% protein respectively, these variables had higher performance in the zootechnical parameters evaluated such as weight gain (WG) and length gain (LS), as for adaptation in captivity the fry were not affected since they presented 95% survival, while T5 was the one that presented a mortality of 5% in total of 90 fry that started and at the end of the investigation ended with 86 experimental units. In the economic analysis, the profitability of the costs of feeding with different levels of commercial protein was evaluated, where it was estimated that the highest profitability was for T1 with 58.20% and a net profit of 0.72USD. Key words: Fish, endemics, feeding, fry, yield